Microalgal cell disruption: effect on the bioactivity and rheology of wheat bread - Nunes, M.Cristiana (2020)
The aim of this study is to investigate the potential of the addition of a microalgal biomass to improve nutritional quality of bread. Microalgae contain a substantial amount of nutrients that are naturally encapsulated within cells, namely proteins, polysaccharides, polyunsaturated fatty acids and pigments (chlorophylls and carotenoids), which are capable of resisting harsh conditions during food processing. However, the cell wall integrity may significantly limit nutrient availability, and microalgal cell disruption is potentially required as a pretreatment. A suspension of a fresh Chlorella vulgaris biomass (0.88 g/L) was disrupted in a high-pressure homogenizer at 340 MPa using 1 and 4 passages. The impact of the cell disruption method was evaluated in terms of the reduction in the number of intact cells and average colony diameter of the remaining cells using flow cytometry and microscopy. Since cell disruption promotes the release of intracellular products, it can impart structural modifications to doughs and breads. Therefore, doughs and breads were prepared with the fresh C. vulgaris biomass (1.0 g of Cv/ 100 g of flour+Cv), the disrupted biomass, or a commercial powder. Doughs were characterized in terms of texture and oscillatory rheology. The texture and colour of breads were also evaluated. Cell wall disruption affected the colour and texture of the breads, resulting in breads with a higher firmness. Furthermore, bioactivity was evaluated, and the reducing power of the bread extracts obtained using the ferric ion reducing antioxidant power assay showed that cell disruption positively modulated the antioxidant capacity